Hydrothermal synthesis of Nb2O5-natural zeolite composite for enhanced adsorptive removal of anionic and cationic dye - Anastasya, Yohana; Muhtar, Sephia Amanda; Munandar, Andika; Rahayu Saraswati, Ayu; Taher, Tarmizi (Greensusmater, 2024)
The imperative to mitigate dye pollution from wastewater has propelled the exploration of efficient adsorbents. This study deals with the preparation and evaluation of Nb2O5-supported natural zeolite (NbX_NZ) for enhanced dye adsorption performance. A facile hydrothermal method was employed to prepare NbX_NZ with varying niobium precursor loadings. Comprehensive material characterization employing FESEM, EDX, TGA, XRD, and FTIR analyses elucidate the successful incorporation of Nb2O5, revealing altered morphological and thermal properties. The adsorption test exhibited a notable augmentation in adsorption capacity for Congo red dye, particularly with the Nb15_NZ sample, showcasing a nearly two-fold increase compared to the parent natural zeolite. The findings underscore the potential of NbX_NZ as promising materials for anionic dye adsorption, paving the way for advancing wastewater treatment solutions and further investigations into metal oxide-modified zeolites.